2013
DOI: 10.1007/s12043-012-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

Fermionic particles with position-dependent mass in the presence of inversely quadratic Yukawa potential and tensor interaction

Abstract: Approximate solutions of the Dirac equation with position-dependent mass are presented for the inversely quadratic Yukawa potential and Coulomb-like tensor interaction by using the asymptotic iteration method. The energy eigenvalues and the corresponding normalized eigenfunctions are obtained in the case of position-dependent mass and arbitrary spin-orbit quantum number k state and approximation on the spin-orbit coupling term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Several studies have demonstrated an interest in relativistic models [19][20][21][22] where the interaction potential is similar to that one of the harmonic oscillator, such as the vibrational spectrum of diatomic molecules [23], the binding of heavy quarks [24,25] and the oscillations of atoms in crystal lattices, by mapping them as a position-dependent mass system [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an interest in relativistic models [19][20][21][22] where the interaction potential is similar to that one of the harmonic oscillator, such as the vibrational spectrum of diatomic molecules [23], the binding of heavy quarks [24,25] and the oscillations of atoms in crystal lattices, by mapping them as a position-dependent mass system [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The Cornell potential is of our particular interest in this work. This Cornell potential consists of a linear plus Coulomb potential, is a particular case of the quark-antiquark interaction, which has one more harmonic type term [28]. The Coulomb potential is responsible by the interaction at small distances and the linear potential leads to the confinement.…”
Section: Introductionmentioning
confidence: 99%
“…This modification in the mass term has been explored in recent decades, for instance, by analysing the behaviour of Dirac particles in the presence of a static scalar and Coulomb potential [91], relativistic scalar particle in the presence of a cosmic string [92]. The quark-antiquark interaction is mapped into a problem of relativistic spinless possessing a position-dependent mass (PDM), where the mass term acquires a contribution given by the interaction potential that consist of linear and harmonic confining potential plus a Coulomb potential term, were investigated in [93]. The Klein-Gordon equation with vector and scalar potentials of Coulomb-types under the influence of non-inertial effects in the cosmic string space-time, were studied by Santos et al [94].…”
Section: Introductionmentioning
confidence: 99%